Global perspective on training and staffing for paediatric cardiac critical care. (4th December 2017) - Bronicki, Ronald A.; Pollak, Uri; Argent, Andrew C.; Kumar, R. Krishna; Balestrini, Maria; Cogo, Paola; Cury Borim, Bruna; De Costa, Kumi; Beca, John; Shimizu, Naoki; Dominguez, Troy E.
Abstract: This manuscript provides a global perspective on physician and nursing education and training in paediatric cardiac critical care, including available resources and delivery of care models with representatives from several regions of the world including Africa, Israel, Asia, Australasia, Europe, South America, and the United States of America.